Natural Killer Cell Interactions with Classical and Non-Classical Human Leukocyte Antigen Class I in HIV-1 Infection - Hölzemer, Angelique; Garcia-Beltran, Wilfredo F.; Altfeld, Marcus (Frontiers in Immunology, 2017)
Natural killer (NK) cells are effector lymphocytes of the innate immune system that are able to mount a multifaceted antiviral response within hours following infection. This is achieved through an array of cell surface receptors surveilling host cells for alterations in HLA class I (HLA-I) expression and other ligands as signs of viral infection, malignant transformation, and cellular stress. This interaction between HLA-I ligands and NK-cell receptors is not only important for recognition of diseased cells, but also mediates tuning of NK-cell effector functions. HIV-1 alters the expression of HLA-I ligands on infected cells, rendering them susceptible to NK cell-mediated killing. However, over the past years, various HIV-1 evasion strategies have been discovered to target NK-cell receptor ligands and allow the virus to escape from NK cell-mediated immunity. While studies have been mainly focusing on the role of polymorphic HLA-A, -B and -C molecules, less is known about how HIV-1 affects the more conserved, non-classical HLA-I molecules HLA-E, -G, and -F. In this review, we will focus on the recent progress in understanding the role of non-classical HLA-I ligands in NK cell-mediated recognition of HIV-1-infected cells.